NMR‐based clinical metabolomics revealed distinctive serum metabolic profiles in patients with spondyloarthritis. (12th August 2020) - Gupta, Latika; Guleria, Anupam; Rawat, Atul; Kumar, Dinesh; Aggarwal, Amita
Abstract: Spondyloarthritis (SpA) is a common rheumatic disorder of the young, marred by delay in diagnosis, and paucity of biomarkers of disease activity. The present study aimed to explore the potential of serum metabolic profiling of patients with SpA to identify biomarker for the diagnosis and assessment of disease activity. The serum metabolic profiles of 81 patients with SpA were compared with that of 86 healthy controls (HCs) using nuclear magnetic resonance (NMR)‐based metabolomics approach. Seventeen patients were followed up after 3 months of standard treatment, and paired sera were analyzed for effects of therapy. Comparisons were done using the multivariate partial least squares discriminant analysis (PLS‐DA), and the discriminatory metabolic entities were identified based on variable importance in projection (VIP) statistics and further evaluated for statistical significance ( p value < 0.05). We found that the serum metabolic profiles differed significantly in SpA as compared with HCs. Compared with HC, the SpA patients were characterized by increased serum levels of amino acids, acetate, choline, N ‐acetyl glycoproteins, N α‐acetyl lysine, creatine/creatinine, and so forth and decreased levels of low‐/very low‐density lipoproteins and polyunsaturated lipids. PLS‐DA analysis also revealed metabolic differences between axial and peripheral SpA patients. Further metabolite profiles were found to differ with disease activity and treatment in responding patients. The results presented in this study demonstrate the potential of serum metabolic profiling of axial SpA as a useful tool for diagnosis, prediction of peripheral disease, assessment of disease activity, and treatment response. Abstract : Metabolomics study using 800 MHz 1H NMR reveals distinctive metabolic signatures with high sensitivity and specificity in the sera of patients with Spondyloarthritis (SpA) compared to those of normal healthy controls. The serum metabolic profiles were further compared between axial and peripheral SpA patients and investigated for their ability to discern disease activity and response to therapy. The obtained metabolic alterations further provided useful insights into the disease mechanisms operating in SpA patients.